BEHAVIORAL ACTIVATION UNTUK MENURUNKAN TINGKAT DEPRESI PADA PASIEN KANKER PAYUDARA - , Mardiana Hayati Solehah ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In 2008, 18,4% Indonesia women suffered from breast cancer, and that amount will increase with higher prevalence in younger women. Getting diagnosed from cancer, the side effects of treatment, high cost medication, changes of physical, financial, psychological, and social aspect, they all highly potential to lead psychological disturbances, especially depression. Depression can lead on decreasing level of activities and quality of life, worst prognosis, susceptible to risky behavior and suicide, more responsive to feel pain, and increasing abnormal growth of cancerâs cells. There are a lot of research that prove the benefit of physical activities for physical and psychological health. Because of that, we need therapy that focus to increase activation. Behavioral activation therapy will be held to encourage patients to be more active to reduce depression level. The aim of this research is to prove effectiveness of behavioral activation therapy for breast cancer patients.to reduce depression level. This research will be given to breast cancer patients who already diagnosed for one year, had already took any kind treatment and medication, and got middle-severe depression score in Beck Depression Inventory-II (BDI-II). This research will use single-case A-B-A design and will be analyzed with visual inspection